The Effect of The Jigsaw Cooperative Learning Model on Student Learning Activities in Science Leassons: Inggris - Samsul Bahri; Amin Mustajab (JIEES : Journal of Islamic Education at Elementary School, 2020)
The science learning process is still predominantly centered on the teacher, the methods and learning models are less varied. In teaching science concepts, it is only obtained from the teacher so that students' insight and activity are lacking. This makes the student bored, passive, and less active so that the learning seem monotonous. The aim of research to determine the effect of the jigsaw model of student learning activities in science lessons. The method used is the experimental method, namely the experimental group and the control group. The experimental group used jigsaw cooperative learning for grade IVA students at SDN 12 Entikong and control class for conventional learning for grade IVB students at SDN 12 Entikong. Based on the research results there is an influence on jigsaw cooperative learning. It is known that the value is 3.063 3,063 tcount > ttabel 1,063 and the average analysis is below 0,866 and the average is 4,225, so that the difference in the average score is 2,545. So it can be concluded that there is an influence on the application of the jigsaw cooperative learning model on the learning activities of fourth grade students of SDN 12 Entikong.